2021
DOI: 10.1177/03331024211053572
|View full text |Cite
|
Sign up to set email alerts
|

A systematic evaluation of primary headache management apps leveraging behavior change techniques

Abstract: Background Mobile health apps have the potential to promote adherence to headache management through the use of evidence-based behavior change techniques (e.g., self-monitoring). While many headache management apps exist, the extent to which these apps include behavior change techniques remains unknown. Thus, the present study systematically evaluated the content and quality of commercially available headache management apps. Methods Headache apps were identified using a systematic search in the Apple App and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…Providers frequently expressed a desire for apps providing behavioral intervention specifically for migraine. Reviews of the mobile health landscape for behavioral migraine therapy suggest a need for expert-reviewed apps and note that migraine-specific apps usually function as electronic headache diaries rather than offering behavioral interventions ( 18 20 ). In a recent review of headache management apps, 55 were identified, and only 18% included relaxation training such as diaphragmatic breathing or progressive muscle relaxation ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Providers frequently expressed a desire for apps providing behavioral intervention specifically for migraine. Reviews of the mobile health landscape for behavioral migraine therapy suggest a need for expert-reviewed apps and note that migraine-specific apps usually function as electronic headache diaries rather than offering behavioral interventions ( 18 20 ). In a recent review of headache management apps, 55 were identified, and only 18% included relaxation training such as diaphragmatic breathing or progressive muscle relaxation ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reviews of the mobile health landscape for behavioral migraine therapy suggest a need for expert-reviewed apps and note that migraine-specific apps usually function as electronic headache diaries rather than offering behavioral interventions ( 18 20 ). In a recent review of headache management apps, 55 were identified, and only 18% included relaxation training such as diaphragmatic breathing or progressive muscle relaxation ( 20 ). Notably, apps with relaxation training did not have self-monitoring components for users to track their headache-related symptoms ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, the Biophilic Design Matrix has been proposed to facilitate the implementation of biophilic attributes by interior designers [ 22 , 159 , 160 ]. Future prospects for therapeutic interior environments can also include integration with digital health technologies for migraines [ 161 , 162 ], chronic pain [ 163 , 164 ] and depression [ 165 , 166 ]. It is appealing to suggest that integrated healthcare systems such as Sanford Health, Kaiser Permanente, Intermountain Healthcare, Trinity Health and others may consider partnerships with architectural firms and interior design companies to create, validate and implement residential and commercial interior environments for people living with diverse chronic diseases.…”
Section: Advancing Therapeutic Interior Design To Improve Healthcare ...mentioning
confidence: 99%
“…Patients may benefit from a referral for headache management interventions that combine digital technologies with health-care provider interactions or recommendations for self-directed digital headache interventions, which may be a more feasible approach in busy clinic settings. Although efficacy testing has only been carried out in a few headache management apps,41,47,48 ratings of headache management apps for inclusion of evidence-based behavioral strategies and relaxation training are available59 and provide a starting point for "prescribing" headache digital interventions and tools for patients and families.…”
mentioning
confidence: 99%